Trabecular Bone Score in Asian-Indian Post-menopausal Women Across the Spectrum of Hyperglycaemia: Insights from a Cross-Sectional Study - Tanushi Aggarwal; Ravi Shah; Rimesh Pal; Ashu Rastogi; Veenu Singla; Sanjay K. Bhadada (Indian Journal of Endocrinology and Metabolism)
Introduction: Type 2 diabetes mellitus (T2DM) increases the risk of fragility fractures, despite the fact that areal bone mineral density (aBMD) is either increased or normal compared to healthy non-diabetic subjects. Hence, the trabecular bone score (TBS) is under investigation in this patient cohort as an alternative metric for the assessment of bone health. The present study aimed to determine TBS in post-menopausal women diagnosed with T2DM and in non-diabetic individuals. Methods: This cross-sectional study enrolled 101 individuals with T2DM and 101 individuals without overt T2DM (43 individuals with pre-diabetes and 58 normoglycaemic individuals). Participants underwent a comprehensive history and physical examination, biochemical investigations, and a dual-energy X-ray absorptiometry (DXA) scan with TBS measurement. Results: Post-menopausal women with T2DM did not exhibit any significant difference in aBMD levels in comparison to those with pre-diabetes or normoglycaemic individuals. Although there was no statistically significant difference in aBMD among the three groups, the mean TBS value was significantly lower in the T2DM group when compared to both comparison groups (P < 0.001). Additionally, glycated haemoglobin (HbA1c) and the duration of diabetes demonstrated a significant negative correlation with TBS. Conclusion: TBS may serve as a valuable tool for assessing bone health in individuals with T2DM, particularly when aBMD does not accurately predict the risk of fragility fractures. Both glycaemic control and the duration of diabetes significantly impact TBS values. In individuals with T2DM, incorporating TBS measurements alongside aBMD assessments could offer a more comprehensive evaluation of their bone health.